Plan estratégico de marketing para el Gobierno Autónomo Descentralizado municipal del cantón Pichincha, provincia de Manabí, periodo 2014-2018 - Chavarría Mendoza, José Miguel (2014)
This paper presents the proposal to identify the key problems facing the municipal GAD of Pichincha in the performance of their management, and then assess the possibility of implementing the strategic marketing planning as a possible solution, evaluating their performance from the goals achieved. As an approach to strategic planning, we note the importance of defining the mission in the first instance the municipality. It is the aim to follow and which function is to plan. The mission of a municipality is social: improving the welfare of citizens. You should always keep this goal to not deviate from the basic guidelines of strategic planning. It is obvious and necessary to begin a process of institution building in the town of Pichincha, than a true political status , help you achieve the institutional conditions for sustainable development of the same , through the promotion of fiscal balance , increased the efficient delivery of public services , the introduction of the concept of strategic planning , improving the investment programming , modernization of the internal systems of municipal administration, modernizing information systems to constituents and momentum a process of prioritization of municipal staff through continuous training concept